Density‐dependent positive feedbacks buffer aquatic plants from interactive effects of eutrophication and predator loss. Issue 11 (24th September 2018) - Donadi, S.; Austin, Å. N.; Svartgren, E.; Eriksson, B. K.; Hansen, J. P.; Eklöf, J. S.
Abstract: Self‐facilitation allows populations to persist under disturbance by ameliorating experienced stress. In coastal ecosystems, eutrophication and declines of large predatory fish are two common disturbances that can synergistically impact habitat‐forming plants by benefitting ephemeral algae. In theory, density‐dependent intraspecific plant facilitation could weaken such effects by ameliorating the amount of experienced stress. Here, we tested whether and how shoot density of a common aquatic plant ( Myriophyllum spicatum ) alters the response of individual plants to eutrophication and exclusion of large predatory fish, using a 12‐week cage experiment in the field. Results showed that high plant density benefitted individual plant performance, but only when the two stressors were combined. Epiphytic algal biomass per plant more than doubled in cages that excluded large predatory fish, indicative of a trophic cascade. Moreover, in this treatment, individual shoot biomass, as well as number of branches, increased with density when nutrients were added, but decreased with density at ambient nutrient levels. In contrast, in open cages that large predatory fish could access, epiphytic algal biomass was low and individual plant biomass and number of branches were unaffected by plant density and eutrophication. Plant performance generally decreased under fertilization, suggesting stressful conditions. Together, these results suggest that intraspecific plant facilitation occurred only when large fish exclusion (causing high epiphyte load) was accompanied by fertilization, and that intraspecific competition instead prevailed when no nutrients were added. As coastal ecosystems are increasingly exposed to multiple and often interacting stressors such as eutrophication and declines of large predatory fish, maintaining high plant density is important for ecosystem‐based management.